Investigation on the trace elemental profile of sewage workers in Kolkata, an Indian megacity - Rajlaxmi Basu; Sidharth Sankar Ram; Arunnangshu Biswas; Siddhartha Sankar Ray; Aniruddha Mukhopadhyay; Anindita Chakraborty; Sudarshan Mathummal; Sila Chakrabarti (SAGE Publishing, 2015)
Background. Environmental pollution has become a global health risk. Exposure to pollutants at the work place, i.e. occupational exposure, is one of the areas that need immediate attention. The civic drainage workers are exposed to pollutants present in the wastewater they handle and most of them are toxic heavy metals. Exposure to such pollutants may be a health hazard, since it can lead to the imbalance in nutrient elements status.§ Design and Methods. In the present study, profiling of trace elements in the blood of drainage worker population from an Indian megacity, Kolkata, was carried out by energy dispersive x-ray fluorescence (EDXRF) and compared with the control group population of the same area. Results. The elements detected by EDXRF spectrometry include P, S, Cl, K, Fe, Cu, Zn, Se, Br, and Rb. By using ANOVA with 5% significance level, we observed significant alterations in the trace elements status, iron over loading, selenium deficiency, and in Cu-Zn ratio. Gender specific variations within the same population were also observed. Conclusions. The results indicate that the drainage workers have altered elemental profile in comparison to that of control population.